Strategic alliances in a manufacturing supply chain: Influence of organizational culture from the manufacturer's perspective. - Sambasivan, Murali; Ching, Nget Yen (Emerald, 2010)
Purpose: The basic purpose of this paper is to establish and test the relationship between organizational culture and strategic alliances in a manufacturing supply chain that consists of alliance companies (manufacturers) and alliance partners (suppliers and customers). The relationships have been analyzed from the manufacturer's perspective. Design/methodology/approach: This paper specifically addresses: the relationship between the culture type of alliance company and the degree of integration (trust, communication, and commitment) between the alliance companies and partners; the relationship between the culture type of alliance company and value creation in the alliance company; and the relationship between the degree of integration and value creation in the alliance company. A questionnaire was constructed and distributed to 109 companies that had some form strategic alliance with their suppliers and/or customers. The data collected were tested using analysis of variance and correlation analysis. Findings: The culture type of the alliance company has a significant effect on the degree of integration and value creation. The degree of integration has a significant relationship with value creation. Specifically, the following have been found: ad hocracy culture favors a higher level of communication and commitment with the suppliers; hierarchy culture favors a higher level of commitment with suppliers and helps build a higher level of trust with customers and suppliers; and clan and ad hocracy cultures help in achieving a higher degree of value creation. Originality/value: Identifying the link between the culture and strategic alliances in a supply chain can help decision makers choose the right kind of alliance partners and decide appropriate strategies that need to be adopted to form and maintain alliances.